2014
DOI: 10.1111/cbdd.12255
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Topoisomerase Inhibition: Antitumor 1,4‐Naphthoquinones as Potential Inhibitors of Human Monoamine Oxidase

Abstract: Monoamine oxidase (MAO) action has been involved in the regulation of neurotransmitters levels, cell signaling, cellular growth, and differentiation as well as in the balance of the intracellular polyamine levels. Although so far obscure, MAO inhibitors are believed to have some effect on tumors progression. 1,4-naphthoquinone (1,4-NQ) has been pointed out as a potential pharmacophore for inhibition of both MAO and DNA topoisomerase activities, this latter associated with antitumor activity. Herein, we demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
1
17
0
1
Order By: Relevance
“…For [30]. Another study reported that other 1,4-naphthoquinones such as menadione (2) and the parent 1,4-naphthoquinone (3), also inhibits the MAO isoforms [31]. An older study reports that 1,4-benzoquinone …”
Section: Introductionmentioning
confidence: 99%
“…For [30]. Another study reported that other 1,4-naphthoquinones such as menadione (2) and the parent 1,4-naphthoquinone (3), also inhibits the MAO isoforms [31]. An older study reports that 1,4-benzoquinone …”
Section: Introductionmentioning
confidence: 99%
“…Each experiment was conducted in triplicate, and IC 50 values are expressed as mean ± standard deviation (SD). It should be noted that in the current and a previous study, the recombinant human MAOs were used as MAO sources, while the MAO inhibition of TMN was investigated using the human gastrointestinal tract (MAO‐A) and liver (MAO‐B) enzymes . Although inhibition data recorded with MAO of one species cannot always be extrapolated to another, it is expected that potencies recorded with the human enzymes, although from different tissues and production techniques (e.g.…”
Section: Methodsmentioning
confidence: 98%
“…A subsequent study has shown that the structurally related menadione ( 2 ), also a 1,4‐naphthoquinone compound, is a MAO inhibitor with selectivity for the MAO‐B isoform ( K i = 0.4 μ m ) over MAO‐A ( K i = 26 μ m ) . Lapachol ( 3 ), a 1,4‐naphthoquinone from natural origin, and norlapachol ( 4 ), semi‐synthetic derivative of lapachol, also proved to inhibit the MAOs, albeit with lower potencies compared to TMN . By acting as topoisomerase inhibitors via DNA intercalation, the 1,4‐naphthoquinone class of compounds is also of interest as potential antitumor agents .…”
Section: The Ic50 Values For the Inhibition Of Recombinant Human Mao‐mentioning
confidence: 99%
“…Nevertheless, scientific interest in this class of compounds has not abated thanks to their positive risk-benefit ratio, especially when combined with anti-tumour therapies, and to their recently demonstrated synergy with biotechnological drugs [12,13]. Indeed, interest in the quinone-based scaffold and its derivatives, either as modulators or as pharmacological tools, has even increased consequent to their involvement in such metabolic pathways as purinergic signalling [14], inhibition of human monoamine oxidase [15], telomerase [16] and vasorelaxation [17].…”
Section: Introductionmentioning
confidence: 99%